2008
DOI: 10.1007/s10735-008-9161-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bilateral adrenalectomy on systemic kainate-induced activation of the nucleus of the solitary tract. Regulation of blood pressure and local neurotransmitters

Abstract: Glutamatergic transmission through metabotropic and ionotropic receptors, including kainate receptors, plays an important role in the nucleus of the solitary tract (NTS) functions. Glutamate system may interact with several other neurotransmitter systems which might also be influenced by steroid hormones. In the present study we analyzed the ability of systemic kainate to stimulate rat NTS neurons, which was evaluated by c-Fos as a marker of neuronal activation, and also to change the levels of NTS neurotransm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Similar effects have been reported by Ferrari et al . () where HR decreased by 22% within 30 min of KA administration. In that study, the bradycardia was not attenuated by adrenalectomy, suggesting that the change in HR was most likely due to enhanced parasympathetic activity as opposed to decreased sympathetic stimulation.…”
Section: Discussionmentioning
confidence: 90%
“…Similar effects have been reported by Ferrari et al . () where HR decreased by 22% within 30 min of KA administration. In that study, the bradycardia was not attenuated by adrenalectomy, suggesting that the change in HR was most likely due to enhanced parasympathetic activity as opposed to decreased sympathetic stimulation.…”
Section: Discussionmentioning
confidence: 90%
“…24,25 Previous studies have shown that systemic KA can decrease HR by 22% within 30 min in rats. 26 In urethane anaesthetised rats, KA administration enhanced autonomic activity with animals experiencing impaired baroreceptor reflex and bradyarrhythmias. 27 Rats died due to profound cardiac dilation leading to hypoperfusion of the heart and brain.…”
Section: Discussionmentioning
confidence: 99%